The Effect Of Fiscal Policy And Foreign Direct Investment On The Economic Growth Of Member Countries Of The Organization Of Islamic Cooperation (Oic) - Rahmat, Andi; Zaniah, Zaniah; Kalalo, Santi; Rudiaman, Rudiaman (Proceedings of International Conference on Islamic Economic Finance and Social Finance (ISSN: XXXX-XXXX) (ESSN: XXXX-XXXX), 2025)
Good economic growth is the main goal of all countries in the world. Economic growth will always be the center of attention and is one of the issues that attracts a lot of world attention. To increase the economic growth of a country, the government can reflect and evaluate making the right policies to carry out national economic recovery, one of which is through fiscal policy. Every country needs capital to finance its development projects.This study aims to analyze the effect of fiscal policy and FDI on the economic growth of member countries of the OIC.The focus of this study is the group of nations known as the D-8 countries. The analysis technique used in this study is panel data regression, which was processed using Eviews 12 software.As a result, The probability value of government expenditure, which is used as a proxy for fiscal policy in this study, is 0.0001. Therefore fiscal policy affects economic growth. The probability result for FDI is 0.0014, which is less than 0.05. This means that FDI has a positive effect on economic growth.